2011
DOI: 10.5507/fot.2011.021
|View full text |Cite
|
Sign up to set email alerts
|

Planktic Cyanobacteria in the Lower Uruguay River, South America.

Abstract: Abstract:The Uruguay River is the second most important river in the Río de la Plata Basin. Taxonomical composition, abundance and distribution of cyanobacteria collected at nine sampling stations in the Lower Uruguay River (Uruguay) were analyzed seasonally from 2006 to 2009. A total of 24 taxa were identified, including 13 Chroococcales, 4 Oscillatoriales and 7 Nostocales species. The genera Dolichospermum and Microcystis presented the highest number of species among the planktic water bloom-forming cyanobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 34 publications
(16 reference statements)
0
13
0
6
Order By: Relevance
“…High abundances of a compactly coiled morphospecies, preliminarily reported as D. cf. pseudocompactum (Ferrari et al 2011), have been repeatedly observed in the river since 2006 (Table 1). It commonly occurs mainly along a lower part of the river during spring and summer time (Ferrari et al 2011).…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…High abundances of a compactly coiled morphospecies, preliminarily reported as D. cf. pseudocompactum (Ferrari et al 2011), have been repeatedly observed in the river since 2006 (Table 1). It commonly occurs mainly along a lower part of the river during spring and summer time (Ferrari et al 2011).…”
Section: Introductionmentioning
confidence: 88%
“…pseudocompactum (Ferrari et al 2011), have been repeatedly observed in the river since 2006 (Table 1). It commonly occurs mainly along a lower part of the river during spring and summer time (Ferrari et al 2011). The identical morphospecies was reported under a name Anabaena cf.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations